Lucinactant for the prevention of respiratory distress syndrome in premature infants. Issue 2 (March 2013) - Jordan, Brian K; Donn, Steven M
Respiratory distress syndrome (RDS) is the leading cause of neonatal morbidity and mortality in premature infants. It is caused by surfactant deficiency and lung immaturity. Lucinactant is a synthetic surfactant containing sinapultide, a bioengineered peptide mimic of surfactant-associated protein B. A meta-analysis of clinical trials demonstrates that lucinactant is as effective as animal-derived surfactants in preventing RDS in premature neonates, and in vitro studies suggest it is more resistant to oxidative and protein-induced inactivation. Its synthetic origin confers lower infection and inflammation risks as well other potential benefits, which may make lucinactant an advantageous alternative to its animal-derived counterparts, which are presently the standard treatment for RDS.